Aung San Suu Kyi's Endeavour And Female Leadership In Luc Besson's The Lady Movie (2011): An Individual Psychological Perspective - Widawanto, Roma, Dr. Phil. Dewi Candraningrum, M.Ed, Nur Hidayat, M.Pd (2014)
This study describes the endeavor and female leadership of Suu Kyi through individual psychological perspective, and analyzes the movie "The Lady" based on its structural elements. The research is conducted by using qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is film The Lady directed by Luc Besson. The secondary data source are the books about individual psychology and the other sources, which are related to the analysis. The method of collecting data is observation and library review. Based on the analysis, the study reveals that there are some motives underlying the endeavor of Aung San Suu Kyi. Fiction finalism deals with Suu Kyi's expectation of her goals of life that motivate her to make a great effort. Inferiority feeling can be seen when Suu Kyi was being arrested in her house. Striving for superiority of Suu Kyi shows when she survives and struggles with a lot of pressures from the government that try to make her fail, although she was sick and also lost her husband. Aung San Suu Kyi's style of life makes her become the first women in Burmese who was brave to be a leader, to take the democracy for her people, although she should lost her husband. She takes all the risks to get freedom for her country and for her people. Her social interest motivates her to communicate and cooperate with others in order to help herself or people surrounding her. Her creative power motives her to have plans to reach her goal or solutions of her problem .